Bidirectional power controller design of PHEV for robust frequency control - Ngamroo, Issarachai; Rattanapornchai, Chalotorn (My University, 2012)
This paper presents a bidirectional power controller design of plug-in hybrid electric vehicle (PHEV) for robust frequency control in the two-area interconnected power system with wind farms. The controller structure is a proportional integral (PI). System uncertainties such as various wind patterns, system parameters variation etc., are modeled by the inverse output multiplicative perturbation. The particle swarm optimization is applied for tuning the PI parameters based on the mixed H2/H∞ control technique. Simulation results confirm the superior performance and robustness of the proposed controller.
Keywords: Frequency control; Mixed H2/H∞ control; Particle swarm optimization; Plug-in hybrid electric vehicle